Screening of factors affecting cellulase production from oil palm empty fruit bunches (OPEFB) by Trichoderma ressei RUT C30 - Abdul Karim, Mohamed Ismail; Yusof, Faridah (s.n, 2012)
Cellulase enzymes is expensive in the market due to the high cost of pure cellulose was used as substrate fermentation in its production. It is an important enzyme in many industries such as food, textile, fuel and pharmaceutical. In this study, oil palm empty fruit bunch (OPEFB) was used as substrate for the production of cellulose by strain RUT C-30 through solid state fermentation (SSF)